THE EFFECT OF MNEMONIC DEVICE METHOD TO TEACH VOCABULARY - Hamid Ahmad (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2016)
This Pre Experimental One Group Pretest-Posttest design was carried out to find the effect of Mnemonic Device Method in teaching vocabulary to the first semester students at the English Education Study Program of IKIP-PGRI Pontianak in the Academic Year of 2016/2017. The population was the first semester students and the sample was B morning class consisted of 26 students. The sampling technique used was cluster random sampling. The instrument used to collect the data was a set of vocabulary test. The data were analyzed by using descriptive statistic and inferential statistic analysis. The findings were: (1) Mnemonic Device Method was effective to teach vocabulary; the mean score of pre-test and post-test were significantly different; and (2) the different between pre-test and post-test scores had strong effects to the students vocabulary mastery especially in the first semester students of English Education Study Program IKIP-PGRI Pontianak.